Orthographic Nativization of Hispanic Content Words in Waray Visayan - Piañar, Robertgie Laprodes (Universitas Siliwangi, 2023)
This linguistic study investigates the orthographic nativization of Hispanic borrowed words in Waray Visayan written discourse. The textual source is a news article from Isumat News Portal written in Waray Visayan titled COVID Laboratory ha EVRMC magtitikang na an operasyon. Through a descriptive research method, the words are lexically analyzed as to content words, English equivalents, root words, Spanish equivalents, native affixes, and nativization processes. The analysis reveals that the Hispanic nouns, verbs, and adjectives borrowed by the Waray Visayan article are nativized through full lexical adoption, changing or replacement of letters, orthographic mutation, and adding of native prefixes and suffixes. Thus, the Spanish loanwords have been Filipinized in the Waray linguistic community where sociocultural, economic, and religious activities exist. This further shows that the Spanish words have found unique structure and expression in the Waray Visayan written discourse, not only in literary narratives like the study of Quebec (2021), but also in non-fiction, news article in particular. In effect, it is recommended to conduct the same study with a bigger number of corpora in both written and spoken discourses in Waray Visayan and across the Philippine languages to explore the reach of Hispanic word borrowing and nativization and to investigate other linguistic changes as they undergo nativization. Keywords: Lexical analysis; word borrowing; nativization; Hispanic words; Waray Visayan language.